Synthesis of Iron Nanoparticle Using Polyphenol Bioreductor from Red Pomegranate Extract - Aditya, Muhammad Hafizh; Sugiarti, Sri; Charlena (Sains Natural: Journal of Biology and Chemistry, 2024)
Nano zero valent iron (nZVI) has been utilized for environmental remediation and raw water treatment. The NaBH4 reductor, utilized in iron nanoparticle synthesis, yielded easily oxidized and agglomerated material. Using polyphenol as a bioreductor resulted in a more stable material. The purpose of this research is to synthesize and compare quality of nZVI utilizing NaBH4 (C-nZVI) to nZVI utilizing polyphenol from spent tea and the peel of pomegranate (G-nZVI) and determine the efficiency of pomegranate peel G-nZVI in reducing dissolved organic matter. The iron nanoparticle was synthesized by reducing FeCl3 salt in a water solvent. C-nZVI material was generated as a black powder, whereas G-nZVI materials were black flakes. The band gap energy values of these three materials indicate that they have reached the nanoscale. All three materials had entire nZVI unitary groups based on its FTIR spectrums. The X-ray diffractogram did not clearly show the core of the phase crystals. The G-nZVI from the peel of pomegranate had a greater distribution and mean material size than the spent tea G-nZVI. Both zeta potentials G-nZVI demonstrate that the materials were stable in the aqueous medium. After two hours of incubation, G-nZVI pomegranate peel at room temperature and dark conditions achieved an optimal dissolved organic matter breakdown rate of 98%.